Traditionalist and Revisionist Madzhabs’ Perspectives Against the Sunni Hadith Criticism Method and Refutation - Abdul Mufid (Jurnal Ushuluddin, 2023)
This research aims to reveal the traditionalist and revisionist madzhabsâ€™ perspectives on the criticism of Sunni hadith. As is well known, traditionalists and revisionists still doubt the authenticity and authority of hadith. According to them, one of the reasons for the unauthenticity of hadith is the inefficiency of the evaluation system and the concept of hadith criticism. Employing a historical approach, this research first analyzed the main reasons for this inefficiency, including the presence of inauthentic hadiths in collections of hadith books, the prevalence of falsification and fiction in hadiths, ignorance of internal criticism by hadith narrators, gaps in the principles the notion of RijÄl science, and the falsifications and distortions in the transmission chain. Moreover, it also discussed the responses of hadith defenders, including the possibility of justifying hadiths that have been considered inauthentic, ignorance of the different linguistic levels of hadiths, the constant efforts of hadith narrators to purify the legacy of hadiths and identify falsifications from the time of their publication, the efforts and attention of expertsâ€™ hadiths on textual examination and rigorous investigation of RijÄl. The research results revealed that although the revisionist madzhab doubted the authenticity of the hadiths compiled by Sunni circles, they admitted that they had compiled were not without selection but had gone through external and internal criticism. Meanwhile, the traditionalist madzhab viewed that hadiths narrated by trusted narrators and considered valid by hadith experts should not be questioned or sorted out based on modern critical methods. This madzhab considered that the method of critique of hadith used by some modern scholars tended to doubt the authority and reliability of hadith and thus threatened the integrity and oneness of religious teachings. Meanwhile, the refutation of Sunni hadith experts against the perspectives of traditionalist madzhab included: (1) historical and social context must be considered in assessing the validity and relevance of a hadith. It was what the traditionalist madzhab ignored; (2) it was necessary to assess the hadith narrators critically; (3) the method of hadith criticism developed over time allowed further disclosure of the authenticity of hadith; (4) Traditionalist madzhabs were frequently inconsistent in their assessment of hadith; and (5) Traditionalist madzhab might be influenced by particular cultural contexts, which could influence the interpretation of hadith and lead to bias